Cell Lineage Choice During Haematopoiesis: A Commemorative Issue in Honor of Professor Antonius Rolink - Rhodri Ceredig (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. This special issue of the International Journal of Molecular Sciences contains a collection of articles by colleagues of Antonius (Ton) Gerardus Rolink (19/04/1953-06/08/2017) and honors Ton's life and profound knowledge of and huge contribution to science. Ton participated in an FP7 Marie Curie Initial Training Network called DECIDE, and partners have submitted articles for this Special Issue. Scientists outside this network have also submitted articles. The articles examine various aspects of how the hematopoietic stem-cell gives rise to the different types of blood and immune cells. These include decision-making by the hematopoietic stem cell and the importance of controlling events within cells and the niches the cell resides in. New insights into these processes at the basic scientific level have given rise to an emerging new model for the development of blood cells. In turn, changes to our understanding of this process have led to new and exciting propositions regarding what goes wrong during the early stages of the development of leukemia.